Iddah for Husbands: A Political Analysis of Islamic Family Law - Abdul Azis (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2023)
This paper explores the concept of iddah for husbands, which is not commonly discussed in mainstream Islamic law interpretations or traditions. This paper also highlights the importance of promoting gender equality and justice in Islamic legal traditions and principles. This article was produced from a literature review, and the main data was obtained from a study of fiqh books and regulations regarding iddah in Indonesia. To strengthen the data and analysis, this paper also uses several important research results and articles related to the issues discussed. A political analysis of Islamic law is the approach used in this paper. This approach is used to highlight the relationship between law and power as well as the need to consider the wider social, cultural, and political context in the interpretation and application of Islamic legal principles. This paper analyzes the political aspects of Islam related to Islamic law and the issue of iddah for husbands. This paper argues that the need for proposals to draft laws governing long-awaited periods for men is urgent and must be accompanied by awareness campaigns and counseling services to ensure successful implementation. Implementation of these laws will require careful consideration of the social context and the potential implications for families and individuals.